The algal growth-limiting nutrient of lakes located at Mexico’s Mesa Central - Fernando W. Bernal-Brooks; José J. Sánchez Chávez; Luis Bravo Inclán; Rubén Hernández Morales; Ana K. Martínez Cano; Owen T. Lind; Laura Dávalos-Lind (Journal of Limnology, 2016)
This paper reports on the algal growth-limiting nutrients of five lakes located on Mexico’s Mesa Central - a topic poorly known in the regional limnology of Mexico. The five case studies involved three contiguous watersheds of Michoacán State and provided a trophic state variation from mesotrophic to hypereutrophic; the case studies included Lakes Zirahuén, Pátzcuaro, Teremendo, Cuitzeo and the Cointzio Reservoir. The fieldwork involved the collection of physical and chemical data (including nutrients) from each case study during the dry and rainy seasons of 2010. Additionally, water samples (1 L) were obtained and filtered (0.45 µm) in the laboratory to keep the nutrient content available for bioassays. The chemical analyses suggested a phosphorus (P) limitation in the Cointzio Reservoir, Lake Teremendo and Lake Zirahuén relative to an N:P>16:1. There was a nitrogen (N) limitation at three sampling stations of Lake Pátzcuaro, with an N:P<16:1. As result of the bioassays conducted in July 2012, the Cointzio Reservoir and Lake Teremendo appeared to be P-limited and Lake Pátzcuaro appeared to be N-limited at three sampling stations. Lake Zirahuén showed seasonal variation, with an N limitation during the dry season and a P limitation during the wet season. Those cases with similar results from both methods confirmed the limiting nutrient identification. Lake Cuitzeo, Lake Zirahuén (dry season), and the shallowest sampling station in Lake Pátzcuaro produced unclear results because of divergent outcomes. In terms of the algal growth potential, the Cointzio Reservoir remained unaltered from one season to the next. However, for most of the lakes (with the exception of Lake Pátzcuaro sites 2 and 4), the rainy season provided a dilution effect. Effective lake management depends on a clear recognition of such elements that are in control of the aquatic productivity. In the area of Michoacán, both N and P may act as limiting nutrients.